+0  
 
0
92
1
avatar

If we express 3x^2 - 6x - 2 + 8x + 14 in the form a(x - h)^2 + k , then what is a + h + k?

 Jul 12, 2021
 #1
avatar+121065 
+2

3x^2  -  6x  - 2  +   8x  +  14   =

 

3x^2  +  2x  + 12

 

3 ( x^2  + (2/3)x  + 4)    complete  the  square on  x inside the parentheses

 

3 ( x^2   +  (2/3)x  +  1/9  +  4  -  1/9)

 

3  [ ( x + 1/3)^2   +  35/9 ]  

 

3 ( x + 1/3)^2   +  35/3

 

a  +  h  +   k  = 

 

3   +  (1/3)   +  35/3   =

 

45/3   =

 

15

 

 

cool cool cool

 Jul 12, 2021

45 Online Users

avatar
avatar